REVIEWS (Heythrop journal, 1973)
Book reviewed in this article: The Meaning of Righteousness in Paul. By J. A. Ziesler. Clement of Alexandria: A Study in Christian Platonism and Gnosticism. By Salvatore R. C. Lilla. Ancient Rhetoric and the Art of Tertullian. By Robert Dick Sider. Tertullian, A Historical and Literary Study. By Timothy David Barnes. Cluniac Monasticism in the Middle Ages. Edited by Noreen Hunt. Papal Judges Delegate in the Province of Canterbury 1198–1254. By Jane E. Sayers. Itinera Ministri Generalis Bernardini De Arezzo (1691–1698). By Philippus De Firenze. The Letters and Diaries of John Henry Newman. Volume XXI, January 1864 to June 1865. Edited by Charles Stephen Dessain and Edward E. Kelly. The Spirituality of Friedrich von Hügel. By Joseph P. Whelan. Dietrich Bonhoeffer: Theologian of Reality. By André Dumas. Contemplation in a World of Action. By Thomas Merton. Merton's Theology of Prayer. By John J. Higgins. Faith and Order Louvain 1971. The Absolute and the Atonement. By Illtyd Trethowan. Religion and the Scientific Future. By Langdon Gilkey. Problems of Religious Knowledge. By Terence Penelhum. An Introduction to Modal Logic. By G. E. Hughes and M. J. Cresswell. Modal Logic and its Applications. By D. Paul Snyder. Deontic Logic: Introductory and Systematic Readings. Edited by Risto Hilpinen. Philosophy as Dramatic Theory. By Julián Marías. Translated from the Spanish by James Parsons. Metaphysical Anthropology: the Empirical Structure of Human Life. By Julián Marías. Translated by Frances M. López-Morillas. Shadows of Heaven. By Gunnar Urang.